حلول الأزمة الاقتصادية في الفقه الإسلام - غائب رعد (Al-Adab Journal, 2018)
This Paper deals with economic crisis Solutions in Islamic Jurisprudence, Modern research is based on the opinions of Scholars and their evidence in the Schools of Islamic Jurisprudence, and the from of firm, Stable Conditions to achieve Individual and Society through the Principles of legality and the Judgments that Protect the Individual from Poverty and Palliative and meet the needs of material and Spiritual aims of this Study to an umber of objectives witch prove that Islamic Jurisprudence, Islamic Jurisprudence, is the Safety valve in the Face of Crises and comprehensive System that regulates the relationship with god and his relationship with his brothers in the Community contain rules Kinds of relations and economic and Financial transactions for he is good for the application of all time because it carries with it the reasons for the success and continuity.